PENENTUAN KADAR AMONIA (NH3) PADA AIR SUNGAI MAHAKAM MENGGUNAKAN SPEKTROFOTOMETER DENGAN METODE FENAT - Kusumastuti, Meidina; Sitorus, Saibun; Gunawan, Rahmat (Jurusan Kimia FMIPA UNMUL, 2022)
Determination of Ammonia Levels (NH3) in Mahakam River Water at 5 points around the city of Samarinda has been carried out. The method used is to use a spectrophotometer by the phenate method. The results obtained at these five points are samples of Mahakam river water (Loa Janan Ilir), Mahakam river water (Samarinda Seberang), Mahakam river water (Sungai Kunjang), Mahakam river water (Samarinda Kota) and Mahakam river water (Sambutan) respectively with a concentration was 0.1043 mg/L; 0.1141 mg/L; 0.1303 mg/L; 0.0812 mg/L and 0.1214 mg/L. These results indicate that the highest ammonia concentration is in the Mahakam River (Sungai Kunjang), which is possible due to the high activity of ships. Keywords: Ammonia, phenate method and Mahakam River